National team rugby player injury types, rates and risk factors over two-years - Mathema, P.; Ranson, C.; Moore, I. (British Journal of Sports Medicine, 2014)
Background: Injury surveillance may provide valuable information regarding relationships between initial and subsequent injuries. Subsequent Injury Categorisation (SIC) may be useful in sports such as rugby that have high rates of re-injury amongst elite players. Objective: To identify types, rates and potential risk factors for injury, and subsequent injury, in international rugby players. Design: Prospective injury surveillance using consensus methods and SIC. Setting: Tier 1 international and professional rugby. Participants: Players from one national team squad over two years. Risk factor assessment: Injury types, rates and severity, according to team (national or club), mechanism and activity (training or match) at time of injury, and SIC. Main outcome measurement: Training and match injury incidence (per 100 days), prevalence (% of players unavailable) and average days-lost per injury were calculated for each variable along with the percentage of injuries within each SIC. Results: Overall incidence was 44/100 days (match 30/100 days, training 9/100 days), prevalence was 21% and 16 days were lost per injury. International incidence was highest (25 vs. 19/100 days), but days-lost per injury was greater for club injuries (19 vs. 14 days). Incidence and prevalence was greatest for international impact injuries (11 vs. 6/100 days, 7 vs. 4%), but there were a similar number of days-lost per injury (21 days). During international campaigns the anterior thigh, knee and lower leg regions had the highest injury rates, whilst on Club duty the hip, knee and shoulder were highest. Twenty-nine percent of the 252 subsequent injuries were coded as being related to a previous injury. Fourteen percent of subsequent injuries were a direct recurrence. Conclusions: High incidence of impact injuries in international rugby may be due to greater number of contact events. Injury prevention strategies may need to target different body areas for international vs. club rugby. SIC analysis may allow subsequent injury risk to be better managed.